Modelagem do Método MCSEM 2.5-D usando elementos finitos em C++ - SOUZA JUNIOR, Ivaldevingles Rodrigues de (2019)
The Marine Controlled Source Electromagnetic (MCSEM) is a geophysical method developed in the 80s to carry out studies of oceanic lithosphere. Currently it is used in the oil industry as a seismic support tool, in order to reduce exploration risks. This work presents the numerical modeling of MCSEM 2.5D using the C ++ programming language, that makes possibe the orientation to object, unlike most of the work done in this area, where modeling is performed with FORTRAN, that is not facing this type of programming. In the construction of the program was applied the technique of finite elements to solve the differential equations that describe the physical behavior of this method, this resulted in dividing the field of geo-electric models in various elements and locally solve the problem, so that the convergence of solution are guaranteed. In addition, we studied the signal behavior of this method, in order to understand how it is sensitive to the presence of a reservoir and how this geometry influences the MCSEM measurements.